Tumor-targeting cell-penetrating peptide, p28, for glioblastoma imaging and therapy - Mander, Sunam; Naffouje, Samer A.; Gao, Jin; Li, Weiguo; Christov, Konstantin; Green, Albert; Bongarzone, Ernesto R.; Das Gupta, Tapas K.; Yamada, Tohru (Frontiers in Oncology, 2022)
Despite recent advances in cancer research, glioblastoma multiforme (GBM) remains a highly aggressive brain tumor as its treatment options are limited. The current standard treatment includes surgery followed by radiotherapy and adjuvant chemotherapy. However, surgery without image guidance is often challenging to achieve maximal safe resection as it is difficult to precisely discern the lesion to be removed from surrounding brain tissue. In addition, the efficacy of adjuvant chemotherapy is limited by poor penetration of therapeutics through the blood-brain barrier (BBB) into brain tissues, and the lack of tumor targeting. In this regard, we utilized a tumor-targeting cell-penetration peptide, p28, as a therapeutic agent to improve the efficacy of a current chemotherapeutic agent for GMB, and as a carrier for a fluorescence imaging agent for a clear identification of GBM. Here, we show that a near-infrared (NIR) imaging agent, ICG-p28 (a chemical conjugate of an FDA-approved NIR dye, indocyanine green ICG, and tumor-targeting p28 peptide) can preferentially localize tumors in multiple GBM animal models. Moreover, xenograft studies show that p28, as a therapeutic agent, can enhance the cytotoxic activity of temozolomide (TMZ), one of the few effective drugs for brain tumors. Collectively, our findings highlight the important role of the tumor-targeting peptide, which has great potential for intraoperative image-guided surgery and the development of new therapeutic strategies for GBM.